Peningkatan Kemampuan Kognitif Melalui Implementasi Media Software Proteus Dalam Setting Cooperative Learning Pada Materi Listrik Dinamis - Tamaela, Elsina S.; Latupeirissa, Asry N.; Sapulete, Heppy (Physikos: Journal of Physics and Physics Education, 2022)
This study aim is to determine the increasingly of cognitive abilities dynamic electrical material through Proteus software media in cooperative learning models for students of SMP Negeri 17 Ambon. The type of research is a quasi-experimental with a pre-test and post-test design. The population of this study were students of class X with a sample of 23 people who were taken randomly. The research data were collected using a dynamic electrical material test instrument that had been validated by two experts. The results of the analysis show that the initial cognitive abilities of students as a whole are in the failed qualification (100%) with an average value of 17.24. Meanwhile, the lowest value was 8.10 and the highest was 28.37. This finding shows that students do not yet have knowledge of dynamic electrical material. The failure of the students was then corrected by using Proteus software media in the cooperative learning model. The results of the analysis show that 26% are in very good qualifications, 22% are in good qualifications, while for sufficient and failed qualifications, respectively 26% with the lowest score of 57, the highest 95 and the average cognitive ability of 80.48. Based on the results of normalized gain analysis obtained an increase in cognitive abilities of 70% in the high category and 30% in the medium category. This finding shows that the integration of Proteus software media is very helpful for students in constructing their knowledge. Through Proteus software media, abstract learning material becomes concrete and makes it easier for students to understand it. This proves that the integration of proteus software learning media in cooperative learning settings can help to improve cognitive abilities well.